Managing Dermatologic Effects of Gender-Affirming Therapy in Transgender Adolescents - Huang C; Gold S; Radi R; Amos S; Yeung H (Dove Medical Press, 2022)
Christina Huang,1,* Sarah Gold,1,* Rakan Radi,1 Seth Amos,1 Howa Yeung1,2 1Department of Dermatology, Emory University School of Medicine, Atlanta, GA, USA; 2Clinical Resource Hub, Veterans Affairs Southeast Network Veterans Integrated Service Network 7, Decatur, GA, USA*These authors contributed equally to this workCorrespondence: Howa Yeung, Department of Dermatology, Emory University School of Medicine, 1525 Clifton Road NE Suite 100, Atlanta, GA, 30322, USA, Tel +1 (404) 727-9838, Fax +1 (404) 727-5878, Email howa.yeung@emory.eduAbstract: Transgender adolescents seek gender-affirming medical care to address gender identity and incongruence. Improved understanding of the dermatologic impact of gender-affirming medical care such as pubertal suppression, hormone therapy, and surgeries can enhance patient outcome. Pubertal suppression treats dysphoria associated with development of secondary sex characteristics, including androgen-driven acne. Gender-affirming hormone therapy influences acne and hair development in transgender adolescents. Dermatologists can help manage skin effects associated with chest binding and gender-affirming hormone therapy and surgery. Provision of patient-centered gender-affirming care in dermatologic and multidisciplinary settings is essential to improve skin and overall outcomes of gender-affirming therapy.Keywords: gender-affirming care, testosterone, estrogen, acne, anti-androgen